PENGARUH SUBSTITUSI TEPUNG LABU KUNING (Cucurbita moschata) TERHADAP KUALITAS BOLU KUKUS - ANGGRAINI, MELISA; Syarif, Winerlis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The kind of the reseach was experimental using complete random design with one factor which the amount of pumpkin flour with composition Â 0%; 15%; 25%; and 35%. The hypothesis showed that there was an effect to the substution of flour pumpkin to the steam cake quality. Substitution of 0% showed volume are very chapped, round shape, very neat, not yellow color, texture is very soft, very fine porous, not flavour pumpkin, sweet and not feel pumpkin, as well as the level of very like. Substitution of 15% showed volume are chapped, slightly rounded, neat, slightly yellow color, soft texture, fine porous, slightly flavour pumpkin, sweet, slightly feel pumpkin, and as wellas the level of like. Substitution of 25% showed volume are rather chap, slightly rounded, slightnly neat, yellow color, texture is rather soft, slightly porous smooth, very flavor pumpkin, sweet, feels pumpkin, and the level of preference. Substitution of 35% showe volume are rather chap, slightly rounded, neat, very yellow color, slightly soft, less porous smooth, very flavorful pumpkin, very sweet, very feels pumpkin and the level of preference rather like. The description above shows the showed the better is substitution 15% .Keywords: substitution, pumpkin flour, steam cake, oganoleptic